Annona muricata aqueous extract suppresses T47D breast cancer cell proliferation - Ika Fidianingsih; Ety Sari Handayani (Universa Medicina, 2014)
BackgroundCancer is a dreadful disease caused by abnormal and uncontrolled cell division. Annona muricata L, also known as soursop, is useful as an anticancer herbal medication since its leaves, seeds and fruits contain active compounds called annonaceous acetogenins. The objective of this study was to scientifically justify the traditional application of soursop for anticancer treatment in the community, by comparing the antiproliferative effect of Annona muricata L leaf, seed and fruit aqueous extracts on T47D breast cancer cells. Methods     This study used an experimental post test trial with control group design. Infusions of soursop leaves, seeds, and fruits collected from Kaliurang, Sleman district, Yogyakarta were used for cytotoxicity tests on T47D cells, in comparison with tamoxifen as standard cancer therapy. Proliferative inhibition was determined by 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide [MTT] assay. The parameter of proliferative inhibition was IC50 which is defined as 50% proliferative inhibition ability of soursop and tamoxifen. Significant differences between groups were determined at p<0.05 by Kruskal-Wallis test. ResultsThe leaves, fruits, and seeds Annona muricata and tamoxifen were proven to be able to inhibit T47D cell proliferation. The IC50 of Annona muricata leaf, seed, fruit aqueous extracts and tamoxifen were 31,384.21 µg/ml; 1.528,800 µg/ml; 329,194.81 µg/ml and 114.52 µg/ml, respectively (p=0.016). The IC50 of Annona muricata aqueous extract was significantly different from that of tamoxifen.ConclusionsThe proliferative inhibition of soursop leaves against T47D breast cancer cells is higher than that of soursop fruits and seeds. Annona muricata fruit, seed, and leaf aqueous extracts were less toxic than tamoxifen